2015
DOI: 10.1364/oe.23.021909
|View full text |Cite
|
Sign up to set email alerts
|

Upconversion luminescence from aluminoborate glasses doped with Tb^3+, Eu^3+ and Dy^3+ under the excitation of 26-μm femtosecond laser pulses

Abstract: We investigated the upconversion luminescence of three aluminoborate glasses doped with Tb(3+), Eu(3+), and Dy(3+) under the excitation of 2.6-μm femtosecond (fs) laser pulses. Efficient upconversion luminescence appearing in the visible light spectral region was observed in all three glasses and the emission spectra are quite similar to those obtained under single photon excitation. From the dependence of the luminescence intensity on the excitation intensity in the low excitation intensity regime, it was rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…It can be noted that upconversion luminescence properties with Fs-laser irradiation for different rare earth elements along with their applications were reported elsewhere. [50][51][52][53][54][55][56][57][58] Such as YVO4 single crystal upconversion luminescence was observed under infrared (IR) Fs-irradiation which resulted in broad characteristic emission in visible region (350-600 nm). 50 For, Ce 3+ doped YAP crystal, upconversion luminescence appeared in both ultraviolet and visible region under a focused 800 nm Fs-laser irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…It can be noted that upconversion luminescence properties with Fs-laser irradiation for different rare earth elements along with their applications were reported elsewhere. [50][51][52][53][54][55][56][57][58] Such as YVO4 single crystal upconversion luminescence was observed under infrared (IR) Fs-irradiation which resulted in broad characteristic emission in visible region (350-600 nm). 50 For, Ce 3+ doped YAP crystal, upconversion luminescence appeared in both ultraviolet and visible region under a focused 800 nm Fs-laser irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…As one of the core constituents in TFTs, the dielectric layer also plays a significance role on the device performance. Recently, some printable dielectric materials were developed for TFTs, such as inorganic oxide, polymers, ion-gel, solid-state electrolyte, and so on . Wu et al reported that poly­(methylsilsesquioxane) (PMSQ) could play as the gate insulator in IGZO TFTs by printable dielectric ink .…”
Section: Printed Tfts On Rigid Substratementioning
confidence: 99%
“…In recent years, owing to the rapid development of femtosecond (fs) lasers and their fabrication technology, which provided intense pulses at higher repetition rates and offered shorter pulse durations than conventional lasers, various MPA upconversion luminescence processes were demonstrated in Tb 3+ -doped ZnO-B 2 O 3 -SiO 2 glass, 6) silicate glass, 7,8) lutetium silicate powers, 9) and alumino-borate glasses. 5) These MPA processes were quite different from the conventional upconversion luminescence processes, the electrons were directly excited from the ground state to the excited state without the assistance of intermediate states.…”
Section: Introductionmentioning
confidence: 96%
“…4) Over the past decades, the upconversion luminescence of Tb 3+ was based on excited state absorption, energy transfer, cooperative upconversion, and photon avalanche. 5) It was largely due to the lack of high-intensity and shorterpulse lasers, which could not provide sufficiently high energy to induce a simultaneous MPA process. Thus, rarely has attention been centered on the upconversion luminescence of Tb 3+ based on simultaneous MPA luminescence.…”
Section: Introductionmentioning
confidence: 99%